Virome diversity and potential sharing of wild mammals in a biodiversity hotspot, Yunnan, China - Yongman Guo; Chao Su; Hanwei Liang; Xueqi Jiang; Ruifu Yang; Junbin Ye; Thomas R. Gillespie; Zihou Gao; Lei Xu (Virology Journal)
Abstract Background Small mammals, including rodents, shrews and moonrats are widespread and serve as natural reservoirs for many viral pathogens. However, the composition and distribution of wild animal viromes remain poorly understood. At least 10,000 virus species have the ability to infect humans, but the vast majority are circulating silently in wild mammals. Understanding the virome profiles of these wild animals is crucial for outbreak preparedness, particularly in regions with high mammalian diversity. Methods In this study, we enriched and extracted viral RNA from fecal samples of 459 wild mammals, representing 16 species, in the Xishuangbanna Dai Autonomous Prefecture of China, a recognized biodiversity hotspot in China. We then performed next-generation sequencing and comprehensive virome analyses across these different animal species. Results We identified 5,346 nearly complete contigs annotated to 64 viral families, with 45 viral families identified in rodents and 46 viral families in shrews and moonrats, showing significant variation in viral diversity across different host species. Among these, 28 viral families were shared across species, including 11 identified viruses that were potential zoonotic pathogens. Additionally, numerous unidentified viral contigs containing the RdRp-gene showing close evolutionary relationships with viral families known to cause infections in animals. Importantly, several viruses detected in these animals, belonging to the family Hepeviridae, Flaviviridae, Astroviridae, Picornaviridae, and Picobirnaviridae, exhibited > 70% nucleotide sequence identity to viruses known to cause diseases in other wildlife species, domestic animals or even humans. Conclusions These findings significantly increase our knowledge of viral diversity and potential viral transmission within rodents and other sympatric small mammals in an emerging disease hotspot, shedding light on the need for continued surveillance of these small mammal populations.